The Effects of STEM Learning Model and Self-efficacy on Students’ Learning Outcome - Awaludin, Asep; Ruhiyat, Yayat; Anriani, Nurul (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
The purpose of this study is to examine if and how students’ sense of self-efficacy correlates with their performance in STEM-related courses. Descriptive verification is the primary research strategy used in this quantitative investigation. All of the students from Banten Health Polytechnic took part in this study. A random sample strategy was used in this study. The sample size for this study was 100 students. Information was gathered via questionnaires for this investigation. Descriptive statistics and inferential statistics, namely PATH analysis with Smart PLS 3.0 software, are used in this investigation. Student learning outcomes were found to be affected by the STEM learning model (p<0.05), self-efficacy was found to be affected by the STEM learning model (p<0.05), and the STEM learning model was found to be affected by the self-efficacy of its students (p<0.05). It is hoped that further study would yield a STEM education approach that will enable all kids to flourish.